DIAGNOSIS OF HEMODYNAMIC CHANGES OF THE LIVER IN CONDITIONS OF BILIARY HYPERTENSION WITH PERFUSION COMPUTED TOMOGRAPHY - V. A. Malakhanov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Diagnosis and treatment of patients with obstructive jaundice syndrome is one of the actual problems of abdominal surgery. The aim of our study was to determine criteria for the development of adverse outcomes in patients with obstructive jaundice, according to CT perfusion. We have analyzed the results of perfusion CT of 47 patients with mechanical jaundice syndrome. All patients were divided into two groups according to severity of the process. The first group (mild) included 29 patients with jaundice duration up to 7 days and the level of total bilirubin up to 150.0 mmol/L. The second group (moderate) included 18 patients with a duration of the disease of more than 7 days and the level of bilirubin more 150.0 mmol/L. Analysis of perfusion CT results showed that in the group of patients with mild jaundice, significant changes in arterial and portal hemodynamics do not occur. In patients in the second group, we revealed expressed reduction of portal hemodynamics up to 50.0 % (p < 0.003). ALP and HPI were increased twofold (p < 0.01). Despite increased arterial fraction, TLP reduced to 25.5 % (p < 0.05). When analyzing the postoperative complications, we observed the development of adverse outcomes only in patients with moderate degree of the pathology. When assessing the perfusion of the liver in patients with adverse outcomes compared with the control group there is a more pronounced decrease in PVP to 68.0% and TLP - up to 40.0% (p < 0.05).